Analysis of Islamic Business Models Based on Spiritual Capital: A Study on MSMEs in Supporting the Green Economy in Tolitoli Regency - Abd. Muzakkir; Ayuwandira M. Morad; Irfan Efendi (FEB Universitas Mulawarman, 2025)
This study aims to analyze the application of Islamic business models based on spiritual capital to Micro, Small, and Medium Enterprises (MSMEs) in Tolitoli Regency, as well as its contribution to green economy practices in the region. Using a descriptive qualitative approach, data was collected through in-depth interviews, observations, and documentation of 52 MSMEs that already have Environmental Management Statement Letters (SPPL) documents. The results of the study show that the majority of MSME actors consciously apply Islamic business principles in their operational activities. Values such as honesty, halal, maximum service, and spirituality in the form of prayer and the belief that work is worship are the main drivers in business decision-making. In addition to reflecting alignment on the aspects of work ethics and welfare, the Islamic business model is also integrated with environmental sustainability practices. This can be seen from the commitment of business actors to waste management, sustainable use of local raw materials, and compliance with environmental regulations through SPPL ownership. The involvement of local governments through training, legality facilitation, and empowerment support has also strengthened the adoption of this business model. This study concludes that Islamic business models based on spiritual capital not only form the foundation of ethics and spirituality in the management of MSMEs, but also play a strategic role in supporting the transformation towards an inclusive and sustainable green economy in affirmative areas such as Tolitoli